Quantum dot studies with time-resolved super-resolution microscopy - Dunlap, Megan Kathryn, author; Van Orden, Alan, advisor; Gelfand, Martin, advisor; Krapf, Diego, committee member; Prieto, Amy, committee member; Szamel, Grzegorz, committee member (Colorado State University. Libraries, 2021)
Quantum dots (QDs) are semiconductor nanoparticles whose optical properties make them ideal candidates for a myriad of applications including fluorescence imaging and light harvesting technologies. They are highly emissive and their stochastic switching between states of low and high intensity, called blinking, lends them particularly well to super-resolution (SR) microscopy studies. This thesis is devoted to the development and application of a SR microscope with exceptionally high temporal resolution, so that the fluorescence lifetime, intensity, and emitter location can be simultaneously monitored. This time-resolved SR microscope is used to characterize CdSe/CdS core/shell QDs and clusters of QDs. Small clusters of ~2-5 QDs exhibited fluorescence intensities and lifetimes indicative of directed energy transfer, and regions were resolved within the clusters that were responsible for donating and accepting energy. Correlated images of the same clusters with scanning electron microscopy were used to verify the true distances between QDs in an attempt to confirm the distance-dependence of the Foerster energy transfer rate. A new analysis method was developed for resolving non-blinking emitters based on the lifetime information accessible with the time-resolved SR microscope.
Keywords: lifetime; quantum dot; super-resolution; maximum likelihood estimation; energy transfer; single photon counting